Free edge failure analysis of laminated composite plate under in-plane tension - Lim, Tiong Hwa. (2008)
The project aims to study the free edge stress distributions response of a laminated composite subjected to an in-plane tension using a numerical finite element analysis software package, ANSYS. A systematic modelling approach was derived, in order to increase the confidence level of the numerical results obtained. A sensitivity study of stress distributions at the free edge zone affected by the mesh refinement was done. Through this study, an optimum mesh density was obtained by the study of the resultant stress convergent plots. Two different modelling techniques are explored, namely, using a full shell to sub-solid and a full solid to sub-solid. The results obtained suggested that there is only a subtle difference between both solutions. Finally, verification of the numerical results with the works of other researchers was performed; a good close matching among the results was observed.